(3Yde CMcGe GdfLhes - (3jMji Hf eMeO Hf CHj GdTcQ, eMjj GdOjf, CHh GdaJM, hjYQa HGdMcje GdeZQHj,J (B680 (3g` s
(3ChdgG (B:s
(3gPg GdQSGFd ai cjajI JMGhjd SfI GdYGde hGdMce YdjgG eeG LQHg GdMceGA GdeJbOehf hGfJNHg GdaVdGA GdeJCNQhf afbhd QCS SfI GdYGde gh hbJ Mdhd GdTeS s
(3BNQgG (B:s
(3hLg BNQ YOOfG ef jhe EaWGQ GdfUGQi Edi dg ef CHjH aeG HdZ CNPfG NeSI agh CPQY EQJaGY Gdfjd hai bhdg SOSg s
(3GdfSNI HgG MhGTs
(3jTJed Ydi LOGhd adcjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B166 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B516s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3Gdadcs